In pursuit of vitamin D in plants - Black, Lucinda; Lucas, R.; Sherriff, Jill; Björn, L.; Bornman, J. (MDPI Publishing, 2017)
Vitamin D deficiency is a global concern. Much research has concentrated on the endogenous synthesis of vitamin D in human skin following exposure to ultraviolet-B radiation (UV-B, 280–315 nm). In many regions of the world there is insufficient UV-B radiation during winter months for adequate vitamin D production, and even when there is sufficient UV-B radiation, lifestyles and concerns about the risks of sun exposure may lead to insufficient exposure and to vitamin D deficiency. In these situations, dietary intake of vitamin D from foods or supplements is important for maintaining optimal vitamin D status. Some foods, such as fatty fish and fish liver oils, certain meats, eggs, mushrooms, dairy, and fortified foods, can provide significant amounts of vitamin D when considered cumulatively across the diet. However, little research has focussed on assessing edible plant foods for potential vitamin D content. The biosynthesis of vitamin D in animals, fungi and yeasts is well established; it is less well known that vitamin D is also biosynthesised in plants. Research dates back to the early 1900s, beginning with in vivo experiments showing the anti-rachitic activity of plants consumed by animals with induced rickets, and in vitro experiments using analytical methods with limited sensitivity. The most sensitive, specific and reliable method for measuring vitamin D and its metabolites is by liquid chromatography tandem mass spectrometry (LC-MS/MS). These assays have only recently been customised to allow measurement in foods, including plant materials. This commentary focuses on the current knowledge and research gaps around vitamin D in plants, and the potential of edible plants as an additional source of vitamin D for humans. © 2017 by the authors; licensee MDPI, Basel, Switzerland.